If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 109 = 12n + -1 Reorder the terms: 109 + 2n = 12n + -1 Reorder the terms: 109 + 2n = -1 + 12n Solving 109 + 2n = -1 + 12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12n' to each side of the equation. 109 + 2n + -12n = -1 + 12n + -12n Combine like terms: 2n + -12n = -10n 109 + -10n = -1 + 12n + -12n Combine like terms: 12n + -12n = 0 109 + -10n = -1 + 0 109 + -10n = -1 Add '-109' to each side of the equation. 109 + -109 + -10n = -1 + -109 Combine like terms: 109 + -109 = 0 0 + -10n = -1 + -109 -10n = -1 + -109 Combine like terms: -1 + -109 = -110 -10n = -110 Divide each side by '-10'. n = 11 Simplifying n = 11
| -24-9x=-78 | | 2*8/2+6/3-12*2 | | 5k+122=16k+12 | | -10-84=-234 | | y=-7*0+1 | | 6x+20=14-68 | | 4*5/2 | | -2x-13=4x+17 | | .50x+0.25(30)=33.5 | | 6x-1=4x+15 | | 11x^2-24x-4=0 | | x+2/2=7 | | 12/4*5 | | 3x-7y=8 | | 9x-12=6+3 | | 8a-3(2a-5)+6= | | 2x-3=13-2x | | (x+1)^1/2=5-x | | -2(4x-1)=8 | | 2x-152=232-10x | | -10x-84=-234 | | 3*(-12)/(-4)+2*(-12-7) | | h=40t+200 | | (3/4)*(x-1) | | -3x+3=-3(2x+3) | | 5g+74=12g+11 | | 7x+3=-7+4x+16 | | 5=3-2 | | -7(-2x+5)=-203 | | -3/110+2 | | 3/5*-1/22 | | 5x+10=82-4 |